The Reconstruction Of Sufi’s Roles In Islamic Teaching In Indonesia: A Critical Reflection Over Religious Radicalism - Romansjach, Aman; Naupal, Naupal (KALAM, 2018)
The phenomenon of religious radicalism has never stopped in the history of humankind up to now. This radicalism is different from the peaceful Islamic teaching that took place during the period that Islam entered Indonesia first time with the role of Sufi in it. This article is  an effort of reconstruction of Sufi’s role in Islamic teaching in Indonesia, a reflection over religious radicalism  with phenomenology approach, tassawuf can be categorized as factual life experience according to Heidegger’s concept.  The aim of this study is to analyize  that tassawuf is relevant in the life of plural society of Indonesia, and solution to human who is inherently homo religious to prevent religious radicalism.